Large-scale 21 cm signal predictions at cosmic dawn with calibrated subgrid galaxy formation. Issue 3 (16th July 2021) - Gillet, N J F; Aubert, D; Mertens, F G; Ocvirk, P
ABSTRACT: The process of heating and reionization of the Universe at high redshifts links small-scale structures/galaxy formation and large-scale intergalactic medium (IGM) properties. Even if the first one is difficult to observe, an observation window is opening on the second one, with the promising development of current and future radio telescopes. They will permit to observe the 21 cm brightness temperature global signal and fluctuations. The need for large-scale simulations is therefore strong to understand the properties of the IGM that will be observed. However, at the same time, the urge to resolve the structures responsible for those processes is important. We introduce in this study a simulation framework of the cosmic dawn and reionization, based on hydrodynamics and radiative transfer code and a simple subgrid galaxy formation process for 1 Mpc-resolution simulations. Here, this model is calibrated on the state-of-the-art simulation CoDaII. This scheme permits us to follow consistently dark matter, hydrodynamics, and radiative transfer evolution on large scales, while the subgrid model deals with the galaxy formation scale, in particular, taking into account the different feedback on the star formation. We process the simulation to produce a simulated 21 cm signal as close as possible to the observations.